PROGRAM PEMBELAJARAN AFKAARUNA LEARNING PACK AL-DIRASAH AL-ISLAMIYYAH (ALP DIRIS) DALAM MEMBENTUK KARAKTER RELIGIUS DI MADRASAH IBTIDAIYAH AFKAARUNA ISLAMIC SCHOOL SLEMAN YOGYAKARTA - Kuni Isna Ariesta Fauziah; Muh. Wasith Achadi (Geneologi PAI: Jurnal Pendidikan Agama Islam, 2021)
This study aims to determine how the afkaaruna learning pack al-dirasah al-islamiyyah learning program can shape the religious character of students. This research uses a qualitative approach. Through primary and secondary data sources. The results of this study: 1) The concept of the ALP Diris learning program is religious learning activities derived from one of the three pillars of the madrasa: Islam, local cultural values, and international, with the aim of covering or complementing religious subjects. 2) The implementation of the ALP Diris program includes various activities such as: religious worship, clothing, memorization of short letters and daily prayers, qiro'atul Qur'an, pole, memorization of asma'ul-husna which is carried out every day through the method role models. 3) The results of the Diris ALP learning program in shaping religious character are said to have been good in implementation. As with Thomas Lickona's theory, which includes: knowing the good, students know the teachings of yaumiyyah worship, how to read and write the Koran properly and correctly. Desiring the good students can understand and love what the teacher has taught. Doing the good students implement activities in the ALP Diris program in their daily lives.